CONFLUENCE OF PRACTICES BETWEEN CONSCIOUS CAPITALISM AND HUMANIZED COMPANIES - de Barros Neto, João Pinheiro; Rodrigues, Roberto Moreira do Nascimento (Seven Editora, 2026)
The growing demand for organizational models that combine economic performance, human well-being, and socio-environmental responsibility highlights the need to understand emerging practices such as conscious capitalism and humanized companies. In this context, this study is justified by the relevance of investigating how these approaches intersect and what impacts they generate in corporate environments. The objective is to analyze the convergence between the practices of humanized companies and conscious capitalism, identifying perceptions, benefits, and challenges associated with their implementation, as well as understanding how such initiatives influence employee well-being and motivation. To this end, an exploratory study was conducted through a survey applied to 40 respondents using an online form composed of objective and open-ended questions. Data were analyzed using descriptive statistics, charts, tables, and word clouds, while complying with ethical research principles. The results indicate that, although participants have partial knowledge of the investigated concepts, they recognize benefits such as increased employee engagement, improved work environment, and strengthened corporate reputation. However, relevant challenges also emerge, including cultural resistance, implementation costs, and lack of technical expertise. It is concluded that integrating these practices enhances sustainable development, promotes more ethical organizational cultures, and contributes to purpose-driven business models, although structural and cultural barriers must still be overcome in future initiatives and research.DOI: https://doi.org/10.56238/sevened2026.008-045